1990
DOI: 10.1128/jcm.28.7.1586-1590.1990
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of nonradiometric BACTEC and improved oxoid signal blood culture systems in a clinical laboratory

Abstract: The BACTEC NR660 blood culture system, which uses infrared spectroscopy to detect carbon dioxide generated by bacterial growth, was compared with the new medium formulation of the Oxoid Signal system. Two trials were conducted: a comparative study of 88 organisms in simulated blood cultures and a clinical trial of 3,321 paired patient blood culture samples. Both trials showed that overall the BACTEC system performed better in the recovery of organisms. The Oxoid system was unable to detect by signal the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The differential white cell count was performed by microscopic examination at 400 and 1000 magnification, counting 100 cells. A sample for blood culture was collected aseptically and a commercial culture system (OXOID SIGNAL Blood Culture System, Oxoid) was used as previously reported (Daley et al, 1990;Rohner et al, 1995). The outcome was recorded for all the sick client-owned calves as 'discharged' or 'died/euthanased'.…”
Section: Collection Of Clinical and Clinical Pathological Datamentioning
confidence: 99%
“…The differential white cell count was performed by microscopic examination at 400 and 1000 magnification, counting 100 cells. A sample for blood culture was collected aseptically and a commercial culture system (OXOID SIGNAL Blood Culture System, Oxoid) was used as previously reported (Daley et al, 1990;Rohner et al, 1995). The outcome was recorded for all the sick client-owned calves as 'discharged' or 'died/euthanased'.…”
Section: Collection Of Clinical and Clinical Pathological Datamentioning
confidence: 99%
“…The results obtained during the first evaluations of the Signal system were inferior ( P <0.0001) to those of BACTEC 6B and 7D combined media [56]. Modification of the bottle headspace atmosphere and agitation of the system during the first 24–48 h of incubation improved the performance of the system [53, 57–59] (Table 2). In spite of these improvements, the single‐bottle Signal system detected less pathogens than systems consisting of two media (aerobic and anaerobic) from the same volume of blood, i.e.…”
Section: Manual Systemsmentioning
confidence: 99%
“…The performance of the Signal manometric blood culture system (Unipath) has already been compared with a variety of conventional and automated methods (Murray et al 1988;Weinstein et al 1988Weinstein et al , 1989Wilson et al 1988;Rohner and Auckenthaler 1989). Three comparisons of the Signal with the Bactec non-radiometric NR-660 system (Becton Dickinson) have been reported (Rimmer and Cabot 1988;Daley et al 1990;Schwabe et al 1990). In the study by Rimmer and Cabot (1988), the Signal system was found to be inferior.…”
Section: Introductionmentioning
confidence: 99%